Constructing tridimensional modeling and radiographic evaluation of diaphyseal fractures in a canine femur for veterinary education - Kleber dos Anjos Lucas; Rodrigo Gomes de Souza; Siham Kassab; Marco Aurélio Pereira Sampaio; Nongnuch Inpanbutr; Yuri Karaccas de Carvalho (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To create tridimensional (3D) anatomical models of diaphyseal fractures in dogs (3D AMDFD) and to evaluate the models from their radiographs. Methods: The study consisted of six stages: preparation of femur from a healthy dog cadaver; digitalization of the bone through a 3D scanner and creation of the base model; creation of a 3D AMDFD based on the image of the base model, 3D modeling carried out to reproduce five different types of diaphyseal fractures; printing the models produced on a 3D printer with a thermoplastic material; insertion of neodymium magnets in the fracture line to allow the assembly and disassembly of the parts; and radiography of 3D AMDFD in lateromedial and craniocaudal positions. Results: The base model and 3D AMDFD had high precision in the replication of bone structures, like the bone in natura. The radiopacity and radiolucency of the 3D AMDFD did not necessarily correspond to the bone densities found in the radiography of the natural canine femur. Conclusion: The 3D AMDFD and their respective radiographs accurately reproduced the anatomical structures and fracture lines.